Estimation of genetic parameters and derivation of economic weights for health and welfare indicators to improve breeding strategies in the Merinoland sheep population - Oberpenning, Jennifer; Justus Liebig University Giessen (My University, 2025)
The aim of this cumulative dissertation is to advance the scientific and practical foundations for sustainable sheep breeding by integrating genetic, phenotypic, and economic perspectives, with a particular focus on health and welfare traits such as tail length. Across three complementary studies, this work investigates (chapter 2) the genetic architecture and trait interrelationships of tail length and growth traits in Merinoland sheep, (chapter 3) the heterogeneity of German sheep production systems and their implications for breeding goal prioritization, and (chapter 4) the development of an enhanced bio‑economic modelling framework to derive economic values for a broad spectrum of breeding traits, including novel welfare and disease resistance traits. Together, these studies contribute to a more holistic understanding of how welfare‑oriented breeding strategies can be implemented without compromising production efficiency or economic viability. The first study provides a detailed quantitative‑genetic analysis of tail length (TL) and its associations with key growth traits. Using single‑trait, multiple‑trait, and structural equation models (SEM), the study demonstrates that TL is highly heritable, indicating strong potential for genetic shortening of tails as an alternative to tail docking. Importantly, SEM approaches reveal that phenotypic pathways linking TL to growth performance differ from the underlying genetic correlations. While the genetic correlations between TL and weight traits are positive, suggesting antagonistic relationships from a breeding perspective, the SEM-based time-lagged phenotypic effects are negative. This implies that longer tails may impair growth due to increased susceptibility to contamination and infection. These findings highlight the importance of modelling trait interdependencies not only genetically, but also through causal phenotypic pathways that reflect environmental and health‑related risk factors. The study thus establishes a methodological and conceptual foundation for integrating welfare traits into breeding programs while accounting for their complex biological relationships. Building on this genetic perspective, the second study shifts focus to the diversity of production environments and management systems within the German sheep sector. Through hierarchical clustering of 25 sheep farms, three distinct production system types are identified, differing in herd size, production orientation, and management philosophy (e.g. organic vs. conventional). Using a contingent valuation approach, the study derives cluster‑specific economic weights for 12 breeding goal traits based on farmers’ willingness to pay for genetic improvement. While most traits show similar valuation across clusters, feed utilization exhibits significant differences, underscoring the influence of production context on economic trait relevance. Notably, all clusters assign substantial importance to the trait category “health and welfare,” including tail length, with values ranging from 24% to 29%. In some clusters, welfare traits are prioritized even above performance traits. These results emphasize that modern breeding goals must be tailored to 4 production system characteristics and increasingly reflect societal and farmer‑driven expectations regarding animal welfare and functional robustness. The third study further deepens the economic evaluation by extending the ECOWEIGHT bio‑economic model to incorporate health and welfare traits more explicitly. The enhanced model allows for the integration of disease incidence, treatment costs, and herd‑level tail‑length status, enabling the derivation of marginal and relative economic values for 15 breeding traits in Merinoland sheep. Fertility and lamb survival traits emerge as the economically most influential, collectively accounting for most of the relative economic value. In contrast, health traits, parasite resistance, tail length, and production traits contribute only marginally to overall economic value in the evaluated research herd, largely due to its exceptionally high health status. Sensitivity analyses altering the proportion of short‑tailed animals reveal only minor shifts in economic values, suggesting that welfare‑oriented breeding for shorter tails can be implemented without substantial economic trade‑offs. The study also highlights the need for broader datasets representing more diverse production environments to ensure generalizable economic evaluations. Taken together, the three studies provide a comprehensive framework for incorporating welfare traits, particularly tail length, into sheep breeding programs. The genetic analyses demonstrate the feasibility of selecting for shorter tails while revealing the importance of accounting for phenotypic pathways linked to health risks. The characterization of production systems underscores that welfare traits are increasingly valued by farmers and should be reflected in breeding goals. Finally, the bio‑economic modelling confirms that incorporating welfare traits does not compromise economic efficiency and can be supported by flexible modelling tools capable of accommodating complex trait patterns. This cumulative work therefore contributes to the development of breeding strategies that align genetic potential, economic viability, and societal expectations for improved animal welfare in modern sheep production.
Keywords: Tierzucht; Schaf; Kurzschwänzigkeit; Betriebswirtschaft; ddc:630; ddc:590